Physical activity in people with COPD, using the National Health and Nutrition Evaluation Survey dataset (2003–2006) - Park, Soo Kyung (2013)
BACKGROUND: People with chronic obstructive pulmonary disease (COPD) are sedentary but the extent of the problem is not fully understood. PURPOSES: This study examines sedentary time and physical activity (PA) and the relative effects of demographic and clinical characteristics on sedentary time and PA in a population-based sample of people with COPD and a comparison group from the general population. METHODS: Subjects were drawn from the National Health and Nutrition Examination Survey dataset (2003–2006). Physical activity was measured by accelerometry. RESULTS: People with COPD were sedentary and spent less time in most levels of PA. Age, gender, race, level of education, working status, shortness of breath, self-reported health, and body mass index were significantly associated with sedentary time or level of PA. CONCLUSION: Findings emphasize the need to decrease sedentary time and increase PA in people with COPD.